2014
DOI: 10.1155/2014/627126
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Three Angiogenic Factors in Systemic Lupus Erythematosus and Their Clinical Significance

Abstract: Our research investigates the serum levels of three angiogenic factors in the AF family, namely, placenta growth factor (PlGF), basic fibroblast growth factor (bFGF), and vascular endothelial growth factor (VEGF), in 54 patients with SLE (SLE group) and 28 healthy controls (normal control) through ELISA measurement. And their interrelationships were also systematically analyzed. The SLE patients were then divided into active SLE group and inactive SLE group according to the SLEDAI score. The results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
1
13
0
2
Order By: Relevance
“…Overexpression of FGF2 has also been shown to be beneficial in the experimental autoimmune encephalomyelitis model of MS [51]. In lupus, FGF2 is positively correlated with disease activity [52]. A recent study compared the protein levels of various growth factors in the cerebrospinal fluid (CSF) of lupus patients relative to subjects with disrupted BBB, such as MS. FGF2 was one of six upregulated genes that predicted lupus using a weighted algorithm [53].…”
Section: Fgf System In Neurological Disordersmentioning
confidence: 99%
“…Overexpression of FGF2 has also been shown to be beneficial in the experimental autoimmune encephalomyelitis model of MS [51]. In lupus, FGF2 is positively correlated with disease activity [52]. A recent study compared the protein levels of various growth factors in the cerebrospinal fluid (CSF) of lupus patients relative to subjects with disrupted BBB, such as MS. FGF2 was one of six upregulated genes that predicted lupus using a weighted algorithm [53].…”
Section: Fgf System In Neurological Disordersmentioning
confidence: 99%
“…VEGF is also required for glomerular hypertrophy and proliferation in response to nephron reduction. Loss of VEGF is associated with glomerulosclerosis and tubulointerstitial fibrosis in the remnant kidney (14). These findings suggest that serum VEGF maybe a useful diagnostic marker of active lupus nephritis.…”
Section: Discussionmentioning
confidence: 75%
“…This supports the idea that serum VEGF level may be a useful marker of disease activity and internal organ involvement in disease pathology. A more recent study observed that serum VEGF negatively correlates with plasma albumin, which suggests that disease activity may result in deterioration of nutritional conditions leading to an increase in serum VEGF levels (14). VEGF is also required for glomerular hypertrophy and proliferation in response to nephron reduction.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-basic is a potent angiogenic factor whose activity is involved in endothelial cell and fibroblast survival, proliferation, migration, and tube formation, together with VEGF [35]. An increased FGF-basic level was reported in lupus and tended to be correlated with disease activity [36].…”
Section: Discussionmentioning
confidence: 99%